Adsorption of Te atoms on Au(1 1 1) and the emergence of an adatom-induced bound state. (8th February 2017) - Schouteden, Koen; Debehets, Jolien; Muzychenko, Dmitry; Li, Zhe; Seo, Jin Won; Van Haesendonck, Chris
Abstract: We report on the adsorption of Te adatoms on Au(1 1 1), which are identified and investigated relying on scanning tunnelling microscopy, Auger electron spectroscopy, and density functional theory. The Te adatoms lift the 23  ×  √3 surface reconstruction of the Au(1 1 1) support and their organization is similar to that of previously reported chalcogen adatoms on Au(1 1 1), which are also known to lift the herringbone reconstruction and can adopt a (√3  ×  √3)R30° structure. The adatoms show strong interaction with the Au(1 1 1) surface, resulting in scattering and confinement of the Au surface state (SS) electrons near the Fermi level. More remarkably, scanning tunnelling spectroscopy reveals the existence of an electronic resonance at high voltages well above the Fermi level. This resonance can be interpreted as a bound state that is split off from the bottom of the Au(1 1 1) bulk conduction band. A similar split-off state may exist for other types of adatoms on metallic surfaces that exhibit a surface band gap.